Odpowiedzi

2010-01-20T18:26:09+01:00
3x - 4y = 7 ----------------------> 3x = 7 - 4y
4x - 3y = 14 ------------------------ x = 7/3 - 4/3 y

4*(7/3 - 4/3 y) - 3y = 14
28/3 - 16/3y - 9/3y = 14
28 - 16y - 9y = 42
-25y = 14
y = -14/25
x = 7/3 - 4/3*(-14/25)
x= 7/3 + 56/75
x= 175/25 + 56/75
x=231/25
1 1 1
2010-01-20T18:26:52+01:00
3x-4y=7 |*(-4)
4x-3y=14 |*3

-12x+16y=-28
12x-9y=42

16y - 9y = 42 - 28

7y = 14 |:7
y= 2


3x-4*2=7
3x-8=7
3x=4+8
3x=12 |:3
x= 4

Odpowiedź: Wartość "x" wynosi 4, wartość "y" wynosi 2.

2010-01-20T18:28:28+01:00
3x-4y=7/x3
4x-3y=14/x(-4)

9x-12y=21
-16x+12y=-56

-7=-35/:(-7)
x=5

3x-4y=7
3x5-4y=7
15-4y=7
-4y=7-15
-4y=-8/:(-4)
y=2
2 3 2